A wide-spectrum antimicrobial coating to fight multi-species biofilms in ventilator-associated pneumonia infections - Alves, Diana Filipa Barros (2021)
This study was supported by the Portuguese Foundation for Science and Technology (FCT) under the scope of the strategic funding of UIDB/04469/2020 unit and BioTecNorte operation (NORTE-01-0145-FEDER-000004) funded by the European Regional Development Fund under the scope of Norte2020 - Programa Operacional Regional do Norte. The authors also acknowledge the support, through the Programa Operacional Competitividade e Internacionalização (COMPETE2020) and by national funds, through the Portuguese Foundation for Science and Technology (FCT), of the POLY-PrevEnTT project (PTDC/BTM-SAL/29841/2017-POCI-01-0145-FEDER-029841).